Single-Cell Analysis Reveals Characterization of Infiltrating T Cells in Moderately Differentiated Colorectal Cancer - Yang, Xi; Qi, Quan; Pan, Yuefen; Zhou, Qing; Wu, Yinhang; Zhuang, Jing; Xu, Jiamin; Pan, Mingyue; Han, Shuwen (Frontiers in Immunology, 2021)
Objective: This study aimed to characterize the tumor-infiltrating T cells in moderately differentiated colorectal cancer. Methods: Using single-cell RNA sequencing data of isolated 1632 T cells from tumor tissue and 1252 T cells from the peripheral blood of CRC patients, unsupervised clustering analysis was performed to identify functionally distinct T cell populations, followed by correlations and ligand-receptor interactions across cell types. Finally, differential analysis of the tumor-infiltrating T cells between colon cancer and rectal cancer were carried out. Results: A total of eightdistinct T cell populations were identified from tumor tissue. Tumor-Treg showed a strong correlation with Th17cells. CD8+TRMwas positively correlated with CD8+IEL.Seven distinct T cell populations were identified from peripheral blood. There was a strong correlation between CD4+TN and CD4+blood-TCM. Colon cancer and rectal cancer showed differences in the composition of tumor-infiltrating T cell populations.Tumor-infiltratingCD8+IEL cells were found in rectal cancer but not in colon cancer, while CD8+ TN cellswere found in theperipheral blood of colon cancer but not in that of rectal cancer. A larger number of tumor-infiltrating CD8+ Tex (88.94%) cells were found in the colon cancer than in the rectal cancer (11.06%). The T cells of the colon and rectal cancers showed changes in gene expression pattern. Conclusions: We characterized the T cell populations in the CRC tumor tissue and peripheral blood.